Large-scale school meal programs and student health: Evidence from rural China - Wang, Jingxi; Hernandez, Manuel A.; Deng, Guoying (Elsevier, 2023)
Reducing urban-rural gaps in child health is one of the most difficult challenges faced by many countries. This paper evaluates the impact of a large-scale school meal program in rural China on the health and nutritional status of students aged 6–16 in compulsory education. We use data from the China Health and Nutrition Survey corresponding to four pre-treatment years (2004, 2006, 2009, and 2011) and one post-treatment year (2015) and find that program participation is, on average, associated with a higher child height-for-age. The impacts are larger among students in a better health condition but small or not significant among the most disadvantaged. We do not observe heterogeneous effects across several individual and household characteristics. We also find positive but not significant effects on Body Mass Index-for-age and weight-for-age. The results suggest that NIP partially improved students' health over the first years of implementation, but more support is needed to achieve broader impacts that effectively reach all vulnerable students.